Constraining the timing and sources of volcanism at the Apollo 12 landing site using new Pb isotopic compositions and crystallisation ages - Snape, J.; Davids, B.; Nemchin, Alexander; Whitehouse, M.; Bellucci, J. (Elsevier Science BV, 2018)
The basaltic suites collected at the Apollo 12 landing site have been interpreted as representing a stratigraphic sequence of volcanic flows emplaced in the Oceanus Procellarum region between approximately 3100–3300 Ma. This study presents Secondary Ion Mass Spectrometry (SIMS) Pb isotopic analyses of samples from each of the basaltic suites, which have been used to constrain precise crystallisation ages and initial Pb isotopic compositions. The new crystallisation ages are consistent with the three main basaltic suites (olivine, pigeonite and ilmenite) being emplaced over a period of approximately 60 million years, and the improved precision of these ages has made it possible to reinterpret the stratigraphic sequence of basalt flows underlying the Apollo 12 landing site. Contrary to previous studies, the three ilmenite basalts are determined as having the oldest ages (with a weighted average of 3187 ± 6 Ma; 2σ) and are, therefore, interpreted as representing the lowest unit in the sequence, underlying the olivine and pigeonite basalts (with an age range constrained by the oldest and youngest pigeonite basalts; 3176 ± 6 Ma and 3129 ± 10 Ma; 2σ). The initial Pb isotopic compositions have been compared with recalculated initial Sr and Nd isotopic compositions, and are consistent with the three main basaltic suites originating from magmatic sources that incorporated different proportions of a common primitive mafic cumulate and the residual trapped liquid fraction remaining after a majority of the lunar magma ocean had crystallised. Our data also demonstrate that the feldspathic basalt (12038) is unique, both in terms of its crystallisation age (3242 ± 13 Ma) and its derivation from a distinct mantle reservoir.